Dossier I: Jeffrey Dahmer: El carnicero de Millwakee. Tipología de asesino serial - Santiso Rodríguez, Martina (Quadernos de criminología, 2023)
Study of Jeffrey Dahmer's case and his classification by various authors in the organized category, others in the disorganized category and some in the mixed one. In this work, an analysis of his case and his «modus operandi» will be carried out in order to determine his classification